ALUR PEMASARAN IKAN LAYANG (Decapterus spp.) DI PESISIR DESA KUBUTAMBAHAN KABUPATEN BULELENG PROVINSI BALI - Naibaho, Trijun Sariwaty; Negara, I Ketut Wija; Wijayanti, Ni Putu Putri (Universitas Pattimura, 2024)
Scads (Decapterus spp.) is one of the main catches of fishermen in Kubutambahan Village caught using slerek. The catch is sold to collectors and retailers. This study aims to assess the marketing flow and marketing efficiency level of kite fish in Kubutambahan Village. This research was conducted from February 2024 to July 2024. The research method used was descriptive quantitative and qualitative methods by conducting observations and interviews at marketing institutions. Based on observations and interviews, two marketing channels were found, the first one, namely kite fish from fishermen will be sold to retailers, and ends at consumers, and the second one, kite fish from fishermen to intermediary traders then to retailers and ends at consumers. The value of marketing margins and marketing costs in marketing channel I is IDR 5,042/kg, and IDR 1,917/kg. The value of marketing margins and costs in marketing channel II is IDR 9,956,-/kg, and IDR 2,168,-/kg. The value of fisherman's share in channel I is 75%, and the value of fisherman's share in marketing channel II is 57.29%. The level of efficiency of kite fish marketing or the percentage of total margin on marketing channel I after calculation is 25%, and the level of efficiency of fish marketing on marketing channel II is 43%, this figure shows that kite fish marketing using marketing channel I is still classified as efficient, and marketing channel II is classified as less efficient, if the percentage of total margin is 0 - 33%, and is said to be less efficient at 34-67% and efficiency is said to be inefficient at 68-100%.